FRI0352 PROBABILITY OF ACHIEVING LOW DISEASE ACTIVITY OR REMISSION WITH APREMILAST TREATMENT AMONG DMARD-NAIVE SUBJECTS WITH ACTIVE PSORIATIC ARTHRITIS. (2nd June 2020) - Mease, P. J.; Kavanaugh, A.; Ogdie, A.; Wells, A. F.; Bergman, M.; Gladman, D. D.; Behrens, F.; Richter, S.; Brunori, M.; Teng, L.; Guerette, B.; Smolen, J. S.
Abstract : Background: Apremilast (APR) is associated with comparable ACR response rates in DMARD-naive vs DMARD-experienced patients (pts) with psoriatic arthritis (PsA). 1, 2 A question that remains is if DMARD-naive pts treated with APR have greater chances of achieving treatment targets than DMARD-experienced pts. cDAPSA is a commonly used treatment target. Objectives: To assess the predictive value of baseline (BL) clinical disease status on achieving long-term cDAPSA treatment targets at Wk 52 among DMARD-naive subjects in PALACE 4; to compare these findings vs those recently reported from the PALACE 1-3 studies in subjects with prior exposure to DMARDs; and to provide further evidence that at a group level, achievement of cDAPSA disease targets with APR is associated with no or mild articular and extra-articular disease activity by Wk 52. Methods: This post hoc analysis included subjects assigned to APR 30 mg twice daily at BL who had available cDAPSA data at BL. We calculated the probabilities of shifting across different cDAPSA categories (remission [REM]: ≤4; low disease activity [LDA]: >4 to ≤13; moderate disease activity [Mod]: >13 to ≤27; high disease activity [HDA]: >27 3 ) from BL to Wk 52. Mean values of articular and non-articular variables (e.g., PASI, SJC/TJC, MASES, dactylitis) from BL to Wk 52 were assessed by cDAPSA category achieved at Wk 52 to determine the association between achievement of targets and control of articular and non-articular manifestations. Results from the current analyses were compared with the previously reported results from PALACE 1-3. Results: A total of 175 subjects receiving APR were included; at BL, 66.3% were in HDA, 31.4% in Mod, and 2.3% were in LDA. Overall, subjects who achieved treatment targets (LDA or REM) by Wk 52 had lower levels of disease activity at BL, as shown by a lower number of swollen and tender joints and lower presence of enthesitis and dactylitis. Higher prevalence of psoriasis-involved body surface area ≥3% at BL was observed. Subjects in Mod at BL were estimated to be more than twice as likely to achieve REM or LDA at Wk 52 vs subjects in HDA at BL; for subjects in LDA at BL, the estimated probability of achieving cDAPSA treatment targets was 100% (Figure). PALACE 4 subjects with LDA and Mod at BL exhibited higher estimated probabilities of achieving treatment targets (100.0% and 61.7%, respectively) than those observed in the DMARD-experienced population of PALACE 1-3 (71.1% and 46.9%). Subjects in PALACE 4 who achieved REM or LDA by Wk 52 showed no or mild articular and extra-articular disease activity by Wk 52, similar to what was observed in the PALACE 1-3 population. 4 Conclusion: DMARD-naive subjects in PALACE 4 who had LDA or Mod at BL had the highest likelihood of achieving treatment targets (cDAPSA REM or LDA) by Wk 52 with continued APR treatment. Results from the current probability analyses revealed higher probability rates than those observed in the DMARD-experienced PALACE 1-3 population; control of articular and extra-articular manifestations was observed in the DMARD-naive and DMARD-experienced populations. References: [1]Wells AF, et al. Rheumatology. 2018;57:1253-63. 2. Kavanaugh A, et al. Arthritis Res Ther. 2019;21:118. 3. Machado PM. Ann Rheum Dis. 2016;75:787-90. 4. Mease PJ, et al. Arthritis Care Res. 2020 Jan 7. Disclosure of Interests: Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Arthur Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB – grant/research support, Alexis Ogdie Grant/research support from: Novartis, Pfizer – grant/research support, Consultant of: AbbVie, BMS, Eli Lilly, Novartis, Pfizer, Takeda – consultant, Alvin F. Wells Grant/research support from: AbbVie, Celgene Corporation, Lilly – grant/research support, Consultant of: AbbVie, Alexion, Amgen, BMS, Celgene Corporation, Horizon, Lilly, Novartis, UCB – consultant, Speakers bureau: AbbVie, Alexion, Amgen, BMS, Celgene Corporation, Horizon, Lilly, Novartis, UCB – speakers bureau, Martin Bergman Shareholder of: Johnson & Johnson – stockholder, Consultant of: AbbVie, BMS, Celgene Corporation, Genentech, Janssen, Merck, Novartis, Pfizer, Sanofi – consultant, Speakers bureau: AbbVie, Celgene Corporation, Novartis, Pfizer, Sanofi – speakers bureau, Dafna D Gladman Grant/research support from: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – grant/research support, Consultant of: AbbVie, Amgen Inc., BMS, Celgene Corporation, Janssen, Novartis, Pfizer, UCB – consultant, Frank Behrens Grant/research support from: AbbVie, Chugai, Janssen, Roche, Pfizer – grant/research support, Consultant of: AbbVie Biotest, Boehringer Ingelheim, Celgene Corporation, Chugai, Eli Lilly, Genzyme, Janssen, Novartis, Pfizer, Roche, UCB – consultant, Speakers bureau: AbbVie, Biotest, BMS, Celgene Corporation, Chugai, Eli Lilly, Genzyme, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Sandoz, UCB - speaker, Sven Richter Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Michele Brunori Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Lichen Teng Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Benoit Guerette Employee of: Amgen Inc. – employment; Celgene Corporation – employment at the time of study conduct, Josef S. Smolen Grant/research support from: AbbVie, Eli Lilly, Janssen, Merck Sharp & Dohme, Pfizer, Roche – grant/research support, Consultant of: AbbVie, Amgen Inc., AstraZeneca, Astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, Medimmune, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Samsung, Sanofi, UCB – consultant, Speakers bureau: AbbVie, Amgen Inc., AstraZeneca, Astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, Medimmune, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Samsung, Sanofi, UCB – speaker